Functionalization of Gold-plasmonic Devices for Protein Capture. (2017) - Battista, E.; Scognamiglio, P.L.; Das, G.; Manzo, G.; Causa, F.; Di Fabrizio, E.; Netti, P.A.
Abstract: Here we propose a straightforward method to functionalize gold nanostructures by using an appropriate peptide sequence already selected toward gold surfaces and derivatized with another sequence for the capture of a molecular target. Large scale 3D-plasmonic devices with different nanostructures were fabricated by means of direct nanoimprint technique. The present work is aimed to address different innovative aspects related to the fabrication of large-area 3D plasmonic arrays, their direct and easy functionalization with capture elements, and their spectroscopic verifications through enhanced Raman and enhanced fluorescence techniques.